Monitoring metabolite change in ice stored ghol fish (Protonibea diacanthus) by using a 1H NMR technique: identification of pyruvate as a spoilage marker. Issue 39 (21st September 2016) - Nair, Ratish R.; Joshi, Nidhi; Boricha, Vinod P.; Haldar, Soumya; Chatterjee, Pabitra B.
Abstract : 1 H NMR spectroscopy based metabolic analysis of ice stored Protonibea diacanthus tissue extracts points to the prospect of pyruvate becoming a probable marker for their quality assessment. Abstract : Proton nuclear magnetic resonance ( 1 H NMR) spectroscopy based metabolic analysis of ghol fish ( Protonibea diacanthus ) tissue extracts was carried out to acquire information on quality changes in fish samples during their prolonged storage in ice soon after sea-catch. This study revealed a wide distribution of metabolic signatures with the post-mortem age of ice stored fish. Up to 4 days (D-4) of ice storage, there were little changes in the concentration of a few selected metabolites such as trimethylammonium oxide (TMAO), creatine/phosphocreatine, and pyruvate; however, the concentration of the latter increased significantly afterwards.